Beckett's Molloy, the Promise of Youth, and the Postwar. Issue 3 (August 2021) - Ross, Stephen
Abstract : This paper argues that Samuel Beckett's Molloy charts the historical transition of the postwar moment in generational terms – terms that themselves had real historical significance in the years immediately following the Allied victory in World War II – ultimately, and uncharacteristically, advancing a youthful figure of promise in young Jacques Moran, Jr. Though Beckett is much more commonly read as an allegorist of existential ambivalence – if not despair – I contend that his first postwar novel must properly be understood as staging history in its confused, agonistic, and frustrating family dynamics. Beckett's rendering of authority, history, and hierarchy in terms of perversion, queerness, and sterility ultimately preserves a futurity centred not precisely on the child per se, but on the emergent figure of the adolescent – the teenager, even, I will venture to claim – avant la lettre : Jacques Moran, Jr.